Three dimensional confocal photoacoustic dermoscopy with an autofocusing sono‐opto probe. Issue 5 (20th January 2022) - Ma, Haigang; Wang, Zhiyang; Zuo, Chao; Huang, Qinghua
Abstract: Photoacoustic dermoscopy (PAD) is uniquely positioned for the diagnosis and assessment of dermatological conditions because of its ability to visualize optical absorption contrast in vivo in three dimensions. In this Letter, we developed a 3D confocal PAD (3D‐CPAD) equipped with an autofocusing sono‐opto probe to facilitate the reconstruction of high‐spatial‐resolution imaging of skin with multilaminate structures in depth direction. The autofocusing sono‐opto probe integrated a 10‐mm electrowetting‐based varifocal lens to automatically control the acoustic and optical confocal length, and an annular ultrasonic detector with a mid‐frequency of 32.8 MHz is coaxially configured for receiving photoacoustic signals. Using this sono‐opto probe, the acoustic and optical confocal length‐shifting range from 7 to 43 mm with high image contrast and spatial resolution in the 3D image reconstruction. Autofocusing property tests and 3D human skin in vivo imaging were carried out to demonstrate the imaging capability of the 3D‐CPAD for potential clinical foreground in noninvasive biopsies of skin disease. Abstract : In dermatology, detailed visualization of the structures of skin is the key to make an accurate diagnosis. Hence, a 3D confocal photoacoustic dermoscopy equipped with an autofocusing sono‐opto probe is developed, which provides an autofocusing‐imaging mode in 3D microscopic imaging of superficial skin layers and imaging at greater depths within intensely scattering deep skin layers. It can be used to characterize melanin and microvessels within human skin, which will assist in better understanding the abnormal degree of skin lesions.